The Impact of Fear of Falling on Functional Independence Among Older Adults Receiving Home Health Services - Katherine A. Lawson OTR, LMSSW, PhD; Eugenia Catalina Gonzalez Ph.D., OTR (Scholarworks @ WMU, 2014)
Background: Falls are the fifth leading cause of death for adults aged 65 years and older. Several intrinsic and extrinsic fall risk factors have been identified, butthere is less understanding of the impact of a fear of falling on falls. Seventy percent of recent fallers and 40% percent of non-fallers report a fear of falling. Therefore, the purpose of this study was to examine the correlation between a fear of falling and a history of falls, as well as the impact on the functional independence of community-dwelling older adults receiving home health services. Methods: The participants completed the Falls Efficacy Scale, the Modified Timed Up and Go Test, self- reported fear of falling, and the KATZ ADL-staircase. The participants were primarily Hispanic females. Results: There was not a significant correlation between a fear of falling and a history of falls. Only participants' age, gender, and the number of medical diagnoses were predictive of past falls. There was a moderate correlation between impaired functional mobility and dependence with activities of daily living (ADL). Additionally, a fear of falling was associated with dependence to perform ADLs as measured objectively. Conclusion: Future studies need to examine the effectiveness of interventions that include dual-task challenges during therapeutic interventions and ADL retraining to reduce fall risk among older adults.